Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2023
DOI: 10.1136/bmjopen-2022-063267
|View full text |Cite
|
Sign up to set email alerts
|

Impact of COVID-19 on care at the end of life during the first months of the pandemic from the perspective of healthcare professionals from different settings: a qualitative interview study (the CO-LIVE study)

Abstract: ObjectivesThe objective of this study is to better understand how the COVID-19 outbreak impacted the different domains of the palliative care approach to end-of-life care from the perspective of healthcare professionals (HCPs) from different professions, working in different settings during the first months of the COVID-19 outbreak in the Netherlands.MethodsAn in-depth qualitative interview study among 16 HCPs of patients who died between March and July 2020 in different healthcare settings in the Netherlands.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 18 publications
(29 reference statements)
0
12
0
Order By: Relevance
“…Findings from interviews with Dutch healthcare providers suggest that the COVID-19 pandemic negatively affected certain aspects of palliative care delivery, mainly in the emotional, spiritual and social domains. 29 However, evidence also suggests that the pandemic may be beneficial to palliative care, by raising awareness of the importance of advance care planning and focusing on individual patient needs and preferences. [29][30][31][32]…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Findings from interviews with Dutch healthcare providers suggest that the COVID-19 pandemic negatively affected certain aspects of palliative care delivery, mainly in the emotional, spiritual and social domains. 29 However, evidence also suggests that the pandemic may be beneficial to palliative care, by raising awareness of the importance of advance care planning and focusing on individual patient needs and preferences. [29][30][31][32]…”
Section: Discussionmentioning
confidence: 99%
“…29 However, evidence also suggests that the pandemic may be beneficial to palliative care, by raising awareness of the importance of advance care planning and focusing on individual patient needs and preferences. [29][30][31][32]…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…During the COVID-19 pandemic, many difficulties arose not only concerning patients and their families but also for healthcare professionals (HCPs) and facilities in providing end-of-life care for COVID-19 patients. 1–6 Infectious disease control measures led to visiting restrictions that caused separation between patients and families 7–12 limited care by HCPs, 12–14 communication difficulties between patients, their families and HCPs, 11 12 15 16 and patient isolation. 17–19 It has been suggested that the high workload for HCPs affected the quality of end-of-life care, prioritising urgent physical care over emotional, social and spiritual aspects.…”
Section: Introductionmentioning
confidence: 99%
“… 17–19 It has been suggested that the high workload for HCPs affected the quality of end-of-life care, prioritising urgent physical care over emotional, social and spiritual aspects. 12 …”
Section: Introductionmentioning
confidence: 99%